Pengaruh Ukuran Perusahaan, Profitabilitas, Rasio Kecukupan Modal, Biaya Pendanaan, dan Efisiensi Operasional Terhadap Risiko Likuiditas Perusahaan Perbankan Yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2020 - S, Ruth Dwijayanti; Hersugondo, Hersugondo (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2022)
The purpose of this research isÂ to prove and analyze the effect of firm size, profitability, capital adequacy ratio, funding costs, and operational efficiency on liquidity risk and credit risk in banking companies listed on the Indonesia Stock Exchange. In this study, the population used were banking companies listed on the Indonesia Stock Exchange, while the sample consisted of 27 banking companies selected using the purposive sampling method. The data analysis method used to prove the truth of the hypothesis is panel data regression which is processed using SPSS 20. The data used is from 2016 to 2020. Based on the results of hypothesis testing it was found that Bank size has a positive significant effect on liquidity risk and has a non-significant positive effect on credit risk. Profitability has an insignificant negative effect on liquidity risk and an significant negative effect on credit risk. The capital adequacy ratio has a significant positive effect on liquidity risk and an insignificant positive effect on credit risk. Funding costs have a significant positive effect on liquidity risk and an insignificant negative effect on credit risk. Operational efficiency has an insignificant negative effect on liquidity risk and an insignificant negative effect on credit risk.